BOVINE COLOSTRUM SUPPLEMENTATION IN INFLAMMATORY BOWEL DISEASE: BENEFITS AND ITS ROLE IN GASTROINTESTINAL HEALTH - Kinga Teper,; Patrycja Świercz,; Konrad Strużek,; Agnieszka Kwiatkowska,; Ewelina Mączka,; Wiktor Tracz,; Sandra Khiralla-Gawlik,; Aleksandra Anna Strzelecka,; Aleksandra Ewa Basak,; Jakub Tomaszewski, (International Journal of Innovative Technologies in Social Science, 2025)
Growing evidence suggests that many gastrointestinal and some systemic diseases involve dysfunction of the mucosal barrier. Colostrum is the milk produced during the first few days after birth. Bovine colostrum, a nutrient-rich fluid containing growth factors, hormones, and paracrine substances, shows promise in promoting mucosal healing in various inflammatory, infectious, and injury-related conditions. This review outlines the structure and function of the intestinal barrier and how its disruption contributes to diseases such as inflammatory bowel disease (IBD).IBD comprises chronic, relapsing disorders with unclear causes, and current treatments -targeting immune dysregulation and microbiota imbalances - remain inadequate. Therapies include anti-inflammatory drugs, immunosuppressants, biologics, and supportive interventions like diet and supplements. We explore bovine colostrum as a potential complementary therapy for IBD, reviewing its active components and their gastrointestinal effects based on in vitro and in vivo studies, while also considering its benefits.